Draft Eighth Five Year Plan 1990-95 Volume : V General Areas Government of Assam - Planning Commission (Planning Commission, 1990)
As per fifth educational survey, there are Primary Schools in 97.17% of the Villages within 1.5 K.M. radius. Subsequent to the survey, about 1000 L.P. Schools provincialised. There is an urgent need to rationalise distribution of teachers and even institutions within the State to provide for access of school facilities to the children in the Village/habitations which are still without Schools.
Government of Assam, Planning and Development Department